PENGEMBANGAN FESTIVAL CAP GO MEH SEBAGAI DAYA TARIK WISATA DI KABUPATEN KETAPANG, KALIMANTAN BARA - Giantino, Elen; Wardi, I Nyoman; Bhaskara, Gde Indra (Jurnal Master Pariwisata (JUMPA); Volume 09, Nomor 02, Januari 2023DO - 10.24843/JUMPA.2023.v09.i02.p14, 2023)
Cap Go Meh Festival is one of the annual cultural festival in Ketapang City, West Borneo. Cap Go Meh is the 15th (fifteenth) day after the Lunar New Year which is the peak of the ethnic Chinese New Year celebration. The organization of Cap Go Meh Festival in Ketapang City has so far become a part of annual agenda as well as Gawai Adat Dayak and Pekan Kebudayaan Melayu. Various attractions in Cap Go Meh Festival that are also displayed are Dragon atrractions, Barongsai attractions, Tatung attractions, float parades, torch parades and lantern parades. The Tatung attraction has its own value in Cap Go Meh Festival because it displays attractions that are the result of cultural acculturation between Chinese and Dayaknese. Cap Go Meh Festival in Ketapang City is one of potentials of regional cultural tourism. The right regional cultural tourism development strategy is needed to develop Cap Go Meh Festival as one of the leading tourist attractions in Ketapang City, considering that Ketapang deserves to be an optional cultural destination in West Borneo Province. The application of the right tourist attraction development strategy can have a positive impact on foreign tourist interest, plus Ketapang City is a coastal city that has potentital for supporting tourism such as nature tourism and marine tourism. Keywords: Cap Go Meh Festival; development strategy; cultural tourism.